Controlling symmetry and localization with an artificial gauge field in a disordered quantum system - Clément Hainaut (Nature Portfolio, 2018)
Periodically kicked rotors are useful in exploring localization phenomenon. Here the authors use ultracold Cs atoms kicked by short laser pulses and show that the periodic modulation results into interference signals as a signature of weak and strong localizations.